Paul : a critical life - Murphy-O'Connor, J. (Jerome), 1935-2013 (Oxford University Press, 1997)
Here Jerome Murphy-O'Connor presents a completely new, and much more vivid and dramatic account of the life of Paul than has ever previously been attempted. From his childhood in Tarsus and his years as a student in Jerusalem to the successes and failures of his ministry, this biography has no peer in terms of its detailed reconstructions of Paul's movements and motives. Traditionally, the Acts of the Apostles has provided the framework for the lives of Paul. In recent years, however, the historical value of the Acts has been called into question. Despite the accuracy of many details, they hav.